Analysis of Wind Energy Potential as A Hybrid Power Plant in Banda Aceh and Surrounding Areas - Ratna Sary; Ahmad Syuhada; Teuku Zulfadli (Politeknik Negeri Lhokseumawe, 2022)
Wind is one of the energy sources developed as new and renewable energy in Aceh Province because of the sufficient wind potential available. In its utilization, wind speed is one of the important and main variables in calculating the amount of energy obtained. This energy will later be combined with energy sources from PLN which have been using fossil fuels. Wind potential in Banda Aceh and its surroundings is very possible to be converted into electrical energy because the average wind speed in Banda Aceh and its surroundings ranges from 4-6 m/s and can blow for approximately 4 to 6 hours per day. The results of the study of the potential of wind energy as a power plant in the Saree area (Aceh Besar District), then obtained an average wind speed in 2017 of 4.2 m/s by generating electrical power of 312 Watt/m2. In 2018 it was 4.6 m/s with an electric power of 341 Watt/m2. While in 2019 it was 5 m/s by generating an electric power of 368 Watt/m2 and the comparison in two other areas, namely Gampong Jawa and Gampong Deah Glumpang Banda Aceh, was obtained by Gampong Jawa with a wind speed of 4.35 m/s by producing 324 Watts/m2 and in Deah Glumpang Village with a wind speed of 3.95 m/s with a power output of 296 Watt/m2